Puberty onset in rural and urban children - Hariadi Edi Saputra; Hakimi Hakimi; Melda Deliana; Siska Mayasari Lubis; Karina Sugih Arto (Indonesian Pediatric Society, 2017)
Background Accelerated pubertal onset has been reported in recent years. Environmental factors are assumed to influence this condition.Objective To assess differences in pubertal onset between children in rural and urban areas, as well as to evaluate body mass index (BMI) and socioeconomic status that affect pubertal onset.Methods This cross-sectional study was conducted in July 2010 at junior high schools in Mandailing Natal and Medan, North Sumatera. Data were collected with purposive sampling of children aged 8 to 13 years. Sexual maturity was assessed by Tanner stage and risk factors was determined by questionnaires. The comparison between pubertal onset in rural and urban areas was assessed by Mann-Whitney U test. The relationships between nutritional status, socioeconomic status, sexual maturity, and pubertal onset were assessed by Spearmanâ€™s correlation.Results Eighty-four subjects (38 boys and 46 girls) from a rural area and 87 subjects (40 boys and 47 girls) from an urban area participated in this study. There were significant differences in mean pubertal age of onset between subjects living in rural vs. urban areas, for both girls and boys [girls: 10.2 vs. 9.5 years, respectively (P=0.008); boys: 11.7 vs. 10.1 years, respectively, (P=0.001)]. We found weak negative correlations between BMI and pubertal onset in boys (r=-0.246; P=0.03) and in girls (r=-0.548; P=0.001). We also found weak negative correlations between socioeconomic status and Â pubertal onset in boys (r=-0.406; P=0.0001) and in girls (r=-0.575; P=0.001).Conclusion Pubertal onset is faster in girls and boys who lived in an urban area. Â There are negative correlations between BMI and socioeconomic status with pubertal onset.